2014
DOI: 10.4102/ojvr.v81i2.718
|View full text |Cite
|
Sign up to set email alerts
|

Serosurveillance of foot-and-mouth disease virus in selected livestock-wildlife interface areas of Tanzania

Abstract: Foot-and-mouth disease (FMD) is caused by a virus of the genus Aphthorvirus of the family Picornaviridae. There is great scientific need for determining the transmission dynamics of FMD virus (FMDV) by drawing more attention to the livestock-wildlife interface areas. A variety of literature suggests that buffalo could serve as reservoir of FMDV in wildlife and cattle. However, many FMDV research studies conducted on experimentally infected cattle as carriers and groups of animal highly susceptible to FMDV (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Seroprevalence of FMD in buffalo and cattle in Tanzania is high. Mkama et al [56] found an overall prevalence of 76.3% (248 of 330) for buffalo and cattle, with the buffalos from western Tanzania having a 100% seroprevalence (29 of 29). Antibodies to FMDV decrease faster in sheep than cattle [57], which could be one explanation for the difference in seroprevalence between small and large ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence of FMD in buffalo and cattle in Tanzania is high. Mkama et al [56] found an overall prevalence of 76.3% (248 of 330) for buffalo and cattle, with the buffalos from western Tanzania having a 100% seroprevalence (29 of 29). Antibodies to FMDV decrease faster in sheep than cattle [57], which could be one explanation for the difference in seroprevalence between small and large ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…In order to maintain commercial trade links, effective vaccination campaigns and stringent control measures have been used to eradicate FMD in Europe and much of South America where the disease was previously endemic. Despite this, the disease continues to circulate on several continents as a consequence of complex epidemiological dynamics and maintenance patterns within both wildlife and livestock (4,5). Sporadic incursions of FMD from these endemic pools continue to threaten countries with disease-free status (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, (14). Serosurveillance of FMDV in wildlife in Tanzania showed that 76.3% of tested buffalo sera samples were positive for FMDV using non-structure FMDV ELISA test for detection of antibodies directed against 3ABC non-structural proteins and confirming natural infection (34). The results of similar studies in wildlife species in Nigeria showed the 3ABC positive reactors in some waterbucks, wildebeests and elands and suggested that wildlife could equally play an important role in the overall epidemiology of FMD in Nigeria (7).…”
Section: Foot-and-mouth Diseasementioning
confidence: 99%